Streptomyces tagetis sp. nov., a chromomycin producing bacteria isolated from the roots of Tagetes patula - Chhetri, Geeta; Kim, Myeong Ji; Kim, Inhyup; Tran, Duc V. H.; Kim, Young-Woo; Kim, Hyun Woo; Seo, Taegun (Frontiers in Microbiology, 2024)
A novel halotolerant actinobacterium, designated as RG38T, capable of producing black extracellular melanin pigment on SP2 agar, was isolated from the roots of Tagetes patula. Comparative analysis of the 16S rRNA gene sequence revealed the highest similarity to Streptomyces collinus NBRC 12759T (99.3%). Phylogenetic analysis showed that strain RG38T clustered within the genus Streptomyces forming a monophyletic cluster with its close relatives. The average nucleotide identity (ANI), digital DNA–DNA hybridization (dDDH), and amino-acid identity (AAI) values between strain RG38T and related species within the genus Streptomyces were below the standard threshold for prokaryotic species delineation. The DNA G + C content of the strain RG38T was determined to be 73.3%. The genome size measured 7,150,598 bp comprising 17 contigs and encompassed 6,053 protein coding genes. AntiSMASH analysis of the whole genome revealed 35 putative biosynthetic gene clusters (BGCs) responsible for various secondary metabolites. Among these clusters, two gene clusters exhibited 100% similarity to the chromomycin A3, albaflavenone, and anthracimycin, respectively. These compounds were reported to possess significant anticancer and antibacterial activities. LC–MS-based analysis, coupled with further isolation studies, confirmed the production of chromomycins A2 (1), A3 (2), and their derivatives, along with their antibiotic activities. These findings underscore the potential of this novel strain as a novel resource for the discovery of diverse antimicrobial compounds. This study is the first to report an antimicrobial compound producing Streptomyces species isolated from medicinal plant T. patula. Based on a polyphasic study, the strain RG38T isolated from an unexplored habitat with a high potential for new natural products represents a novel species within the genus Streptomyces. Accordingly, we propose the name Streptomyces tagetis sp. nov. for this novel species, with the type strain is RG38T (=KCTC 49624T = TBRC 15113T).